Overview of Super-resolution Techniques - Morera Delfín, Leandro (Springer, Cham, 2018)
In the last three decades, multi-frame and single-frame super-resolution and reconstruction techniques have been receiving increasing attention because of the large number of applications that many areas have found when increasing the resolution of their images. For example, in high-definition television, high-definition displays have reached a new level and resolution enhancement cannot be ignored; in some remote sensing applications, the pixel size is a limitation; and in medical imaging, the details are important for a more accurate diagnostic or acquiring high-resolution images while reducing the time of radiation to a patient. Some of the problems faced in this area, that in the future require dealing more effectively, are the inadequate representation of edges, inaccurate motion estimation between images, sub-pixel registration, and computational complexity among others. In this chapter, an overview of the most important methods classified into two taxonomies, multiple- and single-image super-resolution, is given. Moreover, two new techniques for single-image SR are proposed.